Bacteriophages with Potential to Inactivate Aeromonas hydrophila in Cockles: In Vitro and In Vivo Preliminary Studies - João Duarte; Carla Pereira; Pedro Costa; Adelaide Almeida (MDPI AG, 2021)
The recurrent emergence of infection outbreaks associated with shellfish consumption is of extreme importance for public health. The present study investigated the potential application of phages AH-1, AH-4, and AH-5 to inactivate Aeromonas hydrophila, a causative agent of infections in humans associated with bivalve shellfish consumption. The inactivation of A. hydrophila was assessed in vitro, using a liquid culture medium, and in vivo, using artificially contaminated cockles with A. hydrophila ATCC 7966. In the in vitro experiments, all phages were effective against A. hydrophila, but phage AH-1 (with a maximum reduction of 7.7 log colonies forming units CFU/mL) was more effective than phages AH-4 and AH-5 (with reductions of 4.9 and 4.5 log CFU/mL, respectively). The cocktails AH-1/AH-4, AH-1/AH-5, AH-4/AH-5, and AH-1/AH-4/AH-5 were slightly more effective than the single phage suspensions. The phages presented a low emergence rate of phage-resistant mutants. When artificially contaminated cockles were treated in static seawater with phage AH-1, around 44% of the added A. hydrophila (1.0 log CFU/g) was inactivated. The results of this study suggest that phage therapy can be an effective alternative to control human pathogenic bacteria during depuration.